Maximizing vocational teachers' learning: The feedback discussion in the observation of teaching for initial teacher training in further education (UCL Press, 2015)
This paper draws on case-study research that focused on teaching observations conducted as part of vocational teachers' initial teacher training (ITT) in further education (FE) colleges in England. It analyses the post-observation feedback discussion, drawing on a rich sociocultural tradition within work-based learning literature. It argues that the feedback discussion provides a learning space that is particularly important for vocational teachers who cross boundaries from vocational contexts to learn to become teachers. To maximize learning from observation, vocational teachers need time and opportunity to develop their practice with others who mediate their learning and development.